South Manchuria Railway in 1905–1911 - I. R. Khamzin (Научный диалог)
This study investigates Japan's transport and economic policy in Manchuria during the years 1905 to 1911. Utilizing materials from the Russian State Historical Archive, it is revealed that the primary instrument for advancing Tokyo's interests in the region was the pro-government joint-stock company, the South Manchuria Railway, established in 1906. The research addresses the operations of the South Manchuria Railway, the Dairen Port, and maritime shipping conducted by the South Manchuria Railway Company during this period. An overview of Japan's policy to expand railway connectivity is provided, detailing the construction of additional rail routes, including Mukden–Xinmin, Mukden– Andong, and Changchun–Jilin. The competition between the South Manchuria Railway and the Chinese port of Yingkou, as well as cargo transportation along the Liao River, is analyzed, highlighting methods of competitive strategy. The article also reviews the relationship between the South Manchuria Railway and the Chinese Eastern Railway, focusing on policies aimed at integrating the transport capabilities of both railways in Manchuria. The author concludes that by the onset of the Xinhai Revolution in China, Japan had successfully transformed the southern Manchurian region into a zone of its economic monopoly, laying the groundwork for future political and military strategic advancements.